2016
DOI: 10.1016/j.cmet.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Striatal Dopamine Links Gastrointestinal Rerouting to Altered Sweet Appetite

Abstract: Reductions in calorie intake contribute significantly to the positive outcome of bariatric surgeries. However, the physiological mechanisms linking the rerouting of the gastrointestinal tract to reductions in sugar cravings remain uncertain. We show that a duodenal-jejunal bypass (DJB) intervention inhibits maladaptive sweet appetite by acting on dopamine-responsive striatal circuitries. DJB disrupted the ability of recurrent sugar exposure to promote sweet appetite in sated animals, thereby revealing a link b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 39 publications
5
62
0
Order By: Relevance
“…If confirmed, this logic may explain why, over the long term, energy content trumps taste when it comes to food choice. The same group of researchers demonstrated that surgically bypassing the duodenum and jejunum in mice abolished the dopamine-stimulating and appetite-enhancing effects of intragastric glucose (Han et al, 2016), suggesting this as a critical mechanism underlying the reduced sweet craving and carbohydrate intake after bariatric surgery in rodents (Shin and Berthoud, 2011; Tichansky et al, 2011; Wilson-Pérez et al, 2013b). …”
Section: Gastrointestinal Control Of Energy Homeostasismentioning
confidence: 99%
“…If confirmed, this logic may explain why, over the long term, energy content trumps taste when it comes to food choice. The same group of researchers demonstrated that surgically bypassing the duodenum and jejunum in mice abolished the dopamine-stimulating and appetite-enhancing effects of intragastric glucose (Han et al, 2016), suggesting this as a critical mechanism underlying the reduced sweet craving and carbohydrate intake after bariatric surgery in rodents (Shin and Berthoud, 2011; Tichansky et al, 2011; Wilson-Pérez et al, 2013b). …”
Section: Gastrointestinal Control Of Energy Homeostasismentioning
confidence: 99%
“…Postingestive glucose can activate the brain dopamine reward circuit independently of sweet taste,57 and that sweet appetite may even be stimulated by the presence of glucose in the gastrointestinal tract 58…”
Section: Sugar Addiction Might Predispose To Drug Addictionmentioning
confidence: 99%
“…Consequently, there are many pathways by which genetic variations that impact DA signaling can influence food intake and obesity. In addition, emerging work strongly suggests that adiposity, metabolic dysfunction and diets high in saturated fat and sugar produce adaptations in DA function at the molecular, cellular and circuit levels to impact DA-dependent functions ranging from working memory and compulsive behaviors [620] to food preference and nutrient sensing [21, 22] and regulation of glucose metabolism [2326]. Thus DA genetic variants may influence intake not only by conferring initial risk but also by influencing brain adaptations [27, 28].…”
Section: Why Dopamine?mentioning
confidence: 99%